Transoral versus extraoral approach for mandibular angle fractures: A comparative study - Sathya Kumar Devireddy; R.V. Kishore Kumar; Rajasekhar Gali; Sridhar Reddy Kanubaddy; Mallikarjuna Rao Dasari; Mohammad Akheel (Indian Journal of Plastic Surgery)
Introduction: Mandibular fractures represent approximately two-thirds of all the maxillofacial fractures (nearly 70%) out of which fractures of mandibular angle represent for 26-35%. Aim of the Study: The aim of this study is to compare the transoral and extraoral (submandibular) approaches for fixation of mandibular angle fractures. Objectives of Study: The objectives of the following study are to evaluate ease of accessibility, time taken for the procedure, ease of anatomic reduction and complications. Materials and Methods: A prospective study was carried out in 30 patients reporting to the Department of Oral and Maxillofacial surgery, Narayana Dental College and Hospital, Nellore, Andhra Pradesh during the period of months from November 2011 to August 2013 who were randomly divided in two groups based on computer generated simple randomization chart. Group I patients underwent transoral reduction and fixation and Group II patients underwent extraoral reduction and fixation. The ease of accessibility was analysed by visual analogue scale by the operating surgeon, time taken from incision to closure with digital clock, difficulty level index of surgeon based on the time taken for the procedure and approach related complications. Results: The ease of accessibility in Group I was good in 53.3% while in Group II patients approached extraorally it was good in 86.7%. Group I patients approached transorally showed a mean of 49.7 min while that of Group II patients approached extraorally showed a mean of 73.4 min. Group I had a minimum difficulty level index in 60%, moderate difficulty level in 33.3% and severe difficulty level in 6.7% while Group II had a minimum and moderate difficulty level in 46.7% and severe difficulty level in 6.7%. There was 1 (6.7%) complication reported in each group. Conclusion: The statistical analysis of this study concludes that fracture line starting anterior to mandibular third molar and ending at anteroinferior border of the insertion of the masseter muscle or posterior body of mandible can be approached transorally. Fracture line starting posterior or distal to the third molar or posterior to the insertion of the masseter muscle to the angle of the mandible or fracture line extending high in the ramus, extraoral approach provides a better choice for reduction and fixation of the fractured segments with restoration of anatomical and functional occlusion.